2016
DOI: 10.1080/13811118.2016.1164642
|View full text |Cite
|
Sign up to set email alerts
|

Staff Views of an Emergency Department Intervention Using Safety Planning and Structured Follow-Up with Suicidal Veterans

Abstract: The objective of this study is to summarize staff perceptions of the acceptability and utility of the safety planning and structured post-discharge follow-up contact intervention (SPI-SFU), a suicide prevention intervention that was implemented and tested in five Veterans Affairs Medical Center emergency departments (EDs). A purposive sampling approach was used to identify 50 staff member key informants. Interviews were transcribed and coded using thematic analysis. Almost all staff perceived the intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…The Safe Vet project also gathered the opinions of service providers ( N = 50) regarding the practice of SPI via interview (Chesin et al., ). Almost all (98%) participating staff reported that they were satisfied with the SPI‐SFU intervention for various reasons including their increased comfort in discharging patients who presented with suicidal behavior and increased monitoring of suicidal patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Safe Vet project also gathered the opinions of service providers ( N = 50) regarding the practice of SPI via interview (Chesin et al., ). Almost all (98%) participating staff reported that they were satisfied with the SPI‐SFU intervention for various reasons including their increased comfort in discharging patients who presented with suicidal behavior and increased monitoring of suicidal patients.…”
mentioning
confidence: 99%
“…Almost all (98%) participating staff reported that they were satisfied with the SPI‐SFU intervention for various reasons including their increased comfort in discharging patients who presented with suicidal behavior and increased monitoring of suicidal patients. Furthermore, staff reported that the intervention was helpful as it was perceived to decrease suicidal behavior and increase self‐efficacy in managing distress and suicidal thoughts (Chesin et al., ). The SPI is an efficient intervention in terms of its financial cost and time taken to complete and appears to be supported and accepted by clinicians and suicidal patients.…”
mentioning
confidence: 99%
“…Call centers may have greater difficulty implementing SPI if they experience extremely high call volume that severely limits the length of calls or rely predominantly on the provision of referrals rather than crisis counseling. Previous reports have examined the importance of shifting staff's perception of their role and workload in order to support safety planning (Allen et al., ; Chesin et al., ). Our data corroborate that attitudes about SPI are important to the intervention's perceived effectiveness, in that beliefs about SPI's helpfulness and feasibility immediately post‐training predicted subsequent reports of the intervention's effectiveness over the subsequent 9‐month period.…”
Section: Discussionmentioning
confidence: 99%
“…Given this success, crisis hotlines have begun to expand beyond crisis de‐escalation and started to employ brief psychotherapeutic interventions to reduce future suicide risk (Arias, Sullivan, Miller, Camargo, & Boudreaux, ; Boudreaux et al., ; Gould, Cross, Pisani, Munfakh, & Kleinman, ; Stanley et al., , ). These brief interventions typically provide support and psychoeducation, assist with means reduction, and teach coping skills that can be used to weather a future suicidal crisis (Chesin et al., ; Fleischmann et al., ; Johnson, Frank, Ciocca, & Barber, ).…”
mentioning
confidence: 99%
“…In a review of 11 empirical studies of follow-up interventions (i.e., phone, postal letter, postcards, in-person, e-mail, and texting), five demonstrated significant decreases in suicidal behavior ( 39 ). A combined safety planning/structured follow-up intervention (SPI-SFU) in the VA was viewed as acceptable and helpful in preventing future suicidal behavior and promoting treatment engagement ( 40 , 41 ). Social support strategies can also be employed to follow-up with and monitor individuals following suicidal behaviors.…”
Section: The Zs Model and Clinical Trainingmentioning
confidence: 99%